The Influence of Work Discipline and Teamwork on Employee Performance with Organizational Citizenship Behavior as an Intervening Variable at BPJS Branch Offices in Medan Raya - Susy Deliana, Lasmaida; Farida Ferine, Kiki (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
This study aims to analyze the direct and indirect effects of work discipline, teamwork, organizational citizenship behavior (OCB), and employee performance at the BPJS Ketenagakerjaan Branch Office in Medan Raya. The research uses a quantitative approach with a population of 82 employees. The sampling technique used is a saturated sample, where the entire population is used as the sample for this study. Data collection was carried out through questionnaires as the primary data source. The research model was analyzed using path analysis with Smart PLS version 3.3.3. The results of the study indicate that work discipline has a positive but insignificant effect on employee performance, with an original sample value of 0.585 and a P-value of 0.218. On the other hand, work discipline has a negative and significant effect on OCB, with an original sample value of -0.949 and a P-value of 0.000. Teamwork shows a negative but insignificant effect on employee performance, with an original sample value of -0.694 and a P-value of 0.304. However, teamwork has a positive and significant effect on OCB, with an original sample value of 1.720 and a P-value of 0.000. Furthermore, OCB has a positive and significant effect on employee performance, with an original sample value of 1.024 and a P-value of 0.003. Work discipline also has a negative and significant effect on employee performance through OCB, with an original sample result of -0.981 and a P-value of 0.011. Teamwork has a positive and significant effect on employee performance through OCB, with an original sample value of 1.775 and a P-value of 0.001. Thus, OCB plays a crucial role as an intervening variable that mediates the effects of work discipline and teamwork on employee performance.